2010
DOI: 10.5539/ijps.v2n2p81
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Objective Person-Environment Fit: The Dark Side of Intelligence

Abstract: Most previous studies of Person-Environment fit have failed to use objective measures of the work environment that are independent of the person examined. The current research investigated the moderating role of group size (an objective measure obtained from company records), on the relationship between intelligence and pay satisfaction. The intelligence was measured as general intelligence or "g" and "reasoning". On the basis of data from 257 shop-floor workers in a factory, results indicated that group size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
(47 reference statements)
1
0
0
Order By: Relevance
“…It is possible that low Sincerity and Greed-avoidance increase self-promoting behaviors such as estimating higher academic performance, which in turn could affect a decrease in Modesty. Ahmad (2010) demonstrated that people with high cognitive ability thrive best when their ambitions can make impact and can be seen, which was the case in the self-reports in the present study. Furthermore, ambitious and highly cognitive people may have a sense of selfefficacy and mastery, and do not mind using these advantages to get ahead, which could convert into success in present-day schools.…”
Section: Discussionsupporting
confidence: 76%
“…It is possible that low Sincerity and Greed-avoidance increase self-promoting behaviors such as estimating higher academic performance, which in turn could affect a decrease in Modesty. Ahmad (2010) demonstrated that people with high cognitive ability thrive best when their ambitions can make impact and can be seen, which was the case in the self-reports in the present study. Furthermore, ambitious and highly cognitive people may have a sense of selfefficacy and mastery, and do not mind using these advantages to get ahead, which could convert into success in present-day schools.…”
Section: Discussionsupporting
confidence: 76%